Sulfidization flotation performance of malachite in the presence of calcite - Liu, Cheng; Song, Shaoxian; Li, Hongqiang; Ai, Guanghua (Minerals engineering, 2019)
•The effect of calcite on the malachite sulfidization flotation was attempted.•Calcite slime decreased the flotation recovery of malachite.•Calcite slime prevented the adsorption of S species at malachite surface.•Calcite slime fully coated on malachite surface in malachite-system. The effect of calcite on malachite sulfidization flotation was investigated by micro-flotation tests, adsorption, sedimentation and zeta potential test. The micro-flotation results showed that the finer the calcite particles size is, the lower the malachite recovery will be in the sulfidization flotation of malachite at around pH 9.5. The addition of calcite slimes prevented the S species adsorption at malachite surface. Zeta potential distribution measurements confirmed that slimes coating of calcite on malachite surface is detrimental to sulfidization flotation of malachite.